A Qualitative Study on Secondary School Teacher’s Perceptions of Stunting in Majene District, West Sulawesi Province - Sitti Patimah (Universitas Airlangga, 2021)
Background: Stunting remains a major public health problem in Majene, Indonesia. School-based nutrition education is an effective strategy to reduce the prevalence of stunting in all settings. The teachers are the key to implementing the strategy in order to improve the students’ behavior and nutritional status.